Renal Resistive Index is Unsusceptible to Systemic Hemodynamics in Fluid Responsive Critically III Patients - BİLGİLİ, BELİZ; GÜL, FETHİ; CİNEL, İSMAİL HAKKI; ARSLANTAŞ, MUSTAFA KEMAL (GALENOS YAYINCILIK, 2019)
Objective: The primary goal of fluid resuscitation in critically ill patients is to improve oxygen delivery to ensure adequate organ perfusion. Little evidence is known about renal response to fluids in the acute phase, so renal monitoring after the fluid challenge is fundamental during critical care stay. This study aimed to evaluate changes in the renal resistive index (RRI) and to compare these changes with hemodynamic parameters after fluid challenge in fluid responsive critically ill patients. Materials and Methods: Thirty patients older than 18 years who underwent sedation and received mechanical ventilation were prospectively studied. Twenty patients were fluid responsive and were included in the study. An increase of cardiac output (CO) by 10% or more after PLR measured by ultrasonic CO monitor suspected fluid responsiveness. 500 mL of isotonic solution was administered intravenously for 30 minutes. CO measurements were performed at 0, 1 and 30 minutes. RRI and mean arterial pressure (MAP) were measured by Doppler ultrasonography at 0 and 30 minutes. Repeated measures ANOVA method was used for statistical analysis and p<0.05 was considered significant. Results: CO increased significantly after fluid challenge when compared to baseline (from 3.48 +/- 1.14 to 4.34 +/- 1.43 L/min, p<0.001). MAP increased significantly after fluid administration when compared to baseline (80 +/- 19 to 86 +/- 17, p=0.002). RRI did not significantly differ from baseline after fluid challenge (62 +/- 9 to 60 +/- 10, p=0.11). There was a negative correlation between RRI and MAP at baseline and after fluid challenge. Conclusion: The effect of hemodynamic changes on renal perfusion after fluid challenge is controversial. In our study, 500 mL of crystalloid treatment for 30 minutes increased MAP and CO, but did not contribute to the improvement of RRI in patients who were fluid responsive. We found that fluid challenge did not improve RRI in the early phase of the fluid resuscitation in fluid responsive critically ill patients and RRI is unsusceptible to systemic hemodynamic changes during this period.
Keywords: Renal resistive index; macrohemodynamics; renal circulation; fluid responsiveness; ACUTE KIDNEY INJURY; PRESSURE; SURGERY; SHOCK; FLOW